Distribution of phytobenthosis in the presence of an invasive alga Caulerpa cylindracea on the Algerian west coast (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ghellai M, Bachir-Bouiadjra MEA, Dahloum L, Megharbi A, Bachir-Bouiadjra B. 2021. Distribution of phytobenthosis in the presence of an invasive alga Caulerpa cylindracea on the Algerian west coast. Biodiversitas 22: 5644-5653. We have targeted and followed the speed of expansion of Caulerpa cylindracea Sonder 1845 through visiting sixteen sites on the Algerian west coast, out in five provinces which are; Tlemcen, Aïn Témouchent, Oran, Mostaganem and Chlef, where it was listed in eight stations; the coastal lines of Oran and Mostaganem, and in a single station in the province of Aïn Témouchent. The phytosociological surveys were established, made it possible to see the frequency of each identified taxon, mentioning a high degree of disturbance in the appearance of benthic macrophytes regarding the dominance of the invasive species. The calculation of the Shannon index and equitability identify the ecological state of the sites, varies from average (H’ around 3.29 for sites little and not invaded by Caulerpa) to poor (H’: 1.74 for Salamandre), with low macrophytic biodiversity (0.4?E?0.64). The calculation of the Caulerpa racemosa (ICar) index on sandy to rocky substrates with algae does not appear to be a limiting factor for the spread of the invasive species. The previous analyses were validated statistically using Factorial correspondence analysis (FCA), Ascending hierarchical classification (AHC), Principal component analysis (PCA), justifying the unbalanced state according to the degrees of pollution.